Potensi Daun dan Bunga Telang (Clitoria ternatea L.) sebagai Antioksidan - Florentinus Dika Octa Riswanto; Anastasia Melin Fitria Wulandari; Faustina Evania Ngai; Corina Febrianti Isabel; Agatha Kania Ugahari Dyatmika; Filisia Putri Rosari; Dewi Setyaningsih (PT Dexa Medica, 2022)
Indonesia has various traditional plants that are potential to be used as medicinal agents. The telang plant (Clitoria ternatea L.) has been studied regarding its’ potency as a traditional medicine. The parts of the telang plant that are often used are leaves and flowers. Telang leaves and flowers contain several compounds with antioxidant activity including phenolics, flavonoids, anthocyanins, and tannins. Antioxidant activity can be tested using several methods, e.g. DPPH, ORAC, and FRAP. Based on the results of the literature review, it is known that telang leaves and flowers have antioxidant activity and do not show any potential toxicity, therefore they can be considered as safe to be used.